Effect of impregnation of activated carbon with chelating polymer on adsorption kinetics of Pb2+ - Aroua, M.K.; Yin, C.Y.; Lim, F.N.; Kan, W.L.; Daud, W.M.A.W. (Journal of Hazardous Materials, 2009)
The effects of polyethyleneimine (PEI) impregnation on the Pb2+ adsorption kinetics of palm shell-activated carbon and pH profile of bulk solution were investigated. Adsorption data were fitted to four established adsorption kinetics models, namely, pseudo-first-order, pseudo-second-order, Elovich equation and intraparticle diffusion. It was found that PEI impregnation at 16.68 and 29.82 wt PEI/AC increased the Pb2+ uptake rate while the opposite was observed for PEI impregnation at 4.76 and 8.41 wt PEI/AC. The increased uptake rates were due to higher concentration of PEI molecules on the surface of clogged pores as well as varying pore volumes. The adsorption kinetics data fitted the pseudo-second-order model better than the pseudo-first-order model, implying chemisorption was the rate-controlling step. The bulk solution pH generally showed an increasing trend from the use of virgin to PEI-impregnated activated carbon.